Students' Perceptions of Written Examinations and Typed Examinations- A Comparative Study in Gulf University - Nagi, Muskan; Bojiah, Janaki; Al Firas, Mohanad (Journal of Engineering Education Transformations, 2025)
Assessment is inevitable in any kind of formal education because it provides an idea of the amount of learning achieved to both the students and the instructors. Assessment has undergone a drastic change in its form and nature owing to the COVID-19 intervention. During the pandemic, most traditional assessments were reframed to suit to the online mode of conduct. Hence, the typed examinations came into picture replacing the written examinations. Though the students were not trained for the typing exams, they were enforced to take up typed examinations as there was no choice available during that time. This study intends to understand the students’ perceptions with respect to written examinations and typed examinations to identify the preferred mode of giving the examinations. A survey questionnaire comprising closed ended questions on a 5-point Likert was used to get the inputs from the students at Gulf University, Bahrain. Descriptive statistics methodology was adopted after carrying out the Cronbach’s alpha, Pearson’s chi square tests and linear regression on the data. The Statistical Package for Social Sciences (SPSS) v21 was employed for data analysis. The results of the study suggest that the students prefer typing examinations for the ease of typing speed, proficiency in online reading skills, and typing function awareness. The scope of the study is to recommend bringing in the necessary changes in the policies and practices abiding the typing examinations to sustain the preferred mode in an ethical manner. Plus, it suggests addressing the challenges pertaining to the less preferred mode of examinations-handwritten examination for improvisation and further enhancement.